Liver Transplantation for Hepatocellular Carcinoma: A Narrative Review and A Glimpse into The Future - Liu, Hao; Sethi, Vrishketan; Li, Xingjie; Xiao, Yao; Humar, Abhinav (Seminars in Liver Disease, 2024)
Liver transplantation (LT) is a highly effective treatment for carefully selected patients with hepatocellular carcinoma (HCC). In this review, we explored the development of LT selection criteria and organ allocation policies, comparing original data to underscore their historical progression into the intricate task of quantitatively estimating pre- and post-LT survivals. We emphasized the role of biomarkers such as serum alpha-fetoprotein, Des-gamma-carboxy-prothrombin, circulating tumor cells, and circulating tumor DNA in predicting patient outcomes. Additionally, we examined the transplant-associated survival benefits and the difficulties in accurately calculating these benefits. We also reviewed recent advancements in targeted therapy and checkpoint inhibitors for advanced, inoperable HCC and projected their integration into LT for HCC. We further discussed the growing use of living donor liver transplants in the United States and compared its outcomes with those of deceased donor liver transplants. Furthermore, we examined the progress in machine perfusion techniques, which have shown potential in improving patient outcomes and enlarging the donor pool. These advancements present opportunities to enhance LT patient survivals, refine selection criteria, establish new priority metrics, develop innovative bridging and downstaging strategies, and formulate redesigned LT strategies for HCC treatments.
Keywords: liver transplantation; hepatocellular carcinoma; living donor liver transplant; machine perfusion technique; immunotherapy in liver transplantation